Chronic kidney disease and its association with cataracts-A cross-sectional and longitudinal study - Chun-Yen Huang; Jia-In Lee; Chia-Wen Chang; Yao-Hua Liu; Shu-Pin Huang; Shu-Pin Huang; Szu-Chia Chen; Szu-Chia Chen; Szu-Chia Chen; Szu-Chia Chen; Jiun-Hung Geng; Jiun-Hung Geng; et al. (Frontiers Media S.A., 2022)
IntroductionWe aim to explore the association between chronic kidney disease (CKD) and cataracts.MethodsA total of 121,380 participants with adequate information collected from 29 community-based recruitment centers since 2008 were analyzed. The association between CKD and self-reported diagnosed cataracts was examined in a cross-sectional cohort and was validated in a longitudinal cohort of 25,263 participants without cataracts at baseline.Results and discussionOf all participants, cataracts occurred in 503/1,947 (26%) and 10,464/119,433 (9%) subjects in the CKD and non-CKD groups, respectively. Multivariate logistic regression showed that CKD was significantly associated with a higher prevalence of self-reported diagnosed cataracts. In the validation cohort, a higher incidence of cataracts was also noted in the CKD group (65/317, 21%) compared to the non-CKD group (1,964/24,252, 8%) during a mean 47-month follow-up. After adjusting for confounders, subjects with CKD had a 1.498-fold higher risk of incident cataracts than those without CKD (95% confidence interval = 1.114 to 2.013, p value = 0.007). We found that CKD was associated with a higher prevalence of cataracts as well as incident cataracts, which suggests CKD patients and their primary physicians should be aware of this disease and can provide a clue for further exploration of the possible mechanisms and treatments.